2001
DOI: 10.1086/319971
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Optical Variability of Radio-selected Quasars from the FIRST Survey

Abstract: We have obtained single-epoch optical photometry for 201 quasars, taken from the FIRST Bright Quasar Survey, which span a wide range in radio loudness. Comparison with the magnitudes of these objects on the POSS-I plates provides by far the largest sample of long-term variability amplitudes for radio-selected quasars yet produced. We find the quasars to be more variable in the blue than in the red band, consistent with work on optically selected samples. The previously noted trend of decreasing variability wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 29 publications
6
34
1
Order By: Relevance
“…Recent work by Morganson et al (2014) confirm the results of Helfand et al (2000) that quasars are more variable in bluer bands -also consistent to what is found here.…”
Section: Flux Calibrationsupporting
confidence: 90%
“…Recent work by Morganson et al (2014) confirm the results of Helfand et al (2000) that quasars are more variable in bluer bands -also consistent to what is found here.…”
Section: Flux Calibrationsupporting
confidence: 90%
“…These results, and the SF method used to obtain them, have recently been verified for a sample of quasars observed over a 10 year period by MacLeod et al (2010). Furthermore, radio-loud quasars appear more variable than their radio-quiet counterparts (Helfand et al 2001), and the apparent increase in variability for higher redshift quasars is mainly due to the increase of variability with rest-frame frequency and to the increase of rest-frame frequency scanned at high redshift for a given frequency (di Clemente et al 1996).…”
Section: Variability Correlation Plotsmentioning
confidence: 56%
“…In addition, quasar variability is most probably a complex function of several (possibly interdependent) physical parameters such as luminosity, rest-frame wavelength, redshift, black hole mass and time-lag. Helfand et al (2001) have pointed out that "the complex interdependence of the observed variability (of quasars) on wavelength, redshift, bolometric luminosity, radio loudness and possibly other parameters makes it difficult to draw definitive conclusions regarding the physics of the central engine or quasar evolution". Thus, "caveat emptor" should be the watchwords for any discussion of quasar variability dependencies, and thus we employ a method by which these dependencies of variability can be plausibly disentangled.…”
Section: The Structure Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…These relationships are summarized in Helfand et al (2001) and Giveon et al (1999). Numerous studies (e.g., Hawkins 2002;de Vries et al 2003) have shown variability to correlate with time lag.…”
Section: Introductionmentioning
confidence: 99%